2020
DOI: 10.2147/ppa.s246757
|View full text |Cite
|
Sign up to set email alerts
|

<p>Patient Satisfaction with Fentanyl Pectin Nasal Spray in Breakthrough Cancer Pain Management During Radiotherapy for Head and Neck Cancer</p>

Abstract: The severity of breakthrough cancer pain (BTcP) impacts patients' quality of life, increases the risk of anxiety and depression, lowers functional capacities, and may lead to poor compliance with cancer treatments. The aim of the current study was to assess, in a real-life setting, patient satisfaction with a fentanyl-pectin-nasal-spray (FPNS) for BTcP management in head and neck (H&N) cancer patients treated by radiotherapy. Materials and Methods: This non-interventional, prospective study was conducted in 92… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Moreover, we also previously demonstrate that level of satisfaction was significantly associated with the use of fastest onset opioids, especially fentanyl pectin nasal spray (FPNS). 2 , 6 , 7 , 9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we also previously demonstrate that level of satisfaction was significantly associated with the use of fastest onset opioids, especially fentanyl pectin nasal spray (FPNS). 2 , 6 , 7 , 9 …”
Section: Discussionmentioning
confidence: 99%
“… 5 The severity of BTcP impacts patients’ activities of daily living, increases the risk of anxiety and depression, lowers functional capacities, and may lead to poor compliance with cancer treatments. 6–8 …”
Section: Introductionmentioning
confidence: 99%
“…This result suggests that the newly developed topical product was evaluated as more effective than the standard-of-care in reducing pain and increasing relief when skin toxicity was at its highest levels. This is a crucial finding, since pain represents one of the main contributors of poor physical and emotional well-being in cancer patients ( 31 ) and the management of RT-induced pain is fundamental for diminishing the likelihood of treatment interruption ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a reduction in the number of BTcP episodes was documented and patient satisfaction was rated as excellent or good (21,22). Patient satisfaction was also rated as high with fentanyl pectin nasal spray (23). While some reports suggested that fentanyl buccal tablet may have some advantages over other fentanyl formulations, this has not been consistently demonstrated (24).…”
Section: Roos For Treatment Of Btcpmentioning
confidence: 99%
“…During curative radiotherapy, patients with head and neck cancer (irrespective of whether or not they are receiving chemotherapy) have been shown to benefit from the use of intranasal fentanyl, with a decrease in the frequency of incidental BTcP caused by food/liquid swallowing (40). Very recently, high rates of patient satisfaction were also shown with an intranasal formulation of fentanyl in patients undergoing radiotherapy who are at high risk of mucositis (23).…”
Section: Mucositis or Oral Intolerancementioning
confidence: 99%